What insects do, and why - Piper, Ross (Princeton University Press, 2021)
A beautifully illustrated look at the lives and mind-boggling behaviors of insects: What Insects Do, and Why. It takes you on an unforgettable tour of the insect world, presenting these amazing creatures as you have never seen them before. This stunningly illustrated guide explores how insects live, ranging from elegant displays of courtship to brutal acts of predation, and provides insights into the marvelous diversity of insects all around us. Along the way, Ross Piper discusses insect evolution, reproduction and life cycles, feeding strategies, defenses, sociality, parasite-host interactions, human impacts on insects, and more.